The effect of butterfly pea flower on total cholesterol level in male wistar strain rats induced by high fat diet - Trisnadi, Reza Adityas; Kushartanti, BM Wara; Ambardini, Rachmah Laksmi; Chodidjah; Trisnadi, Setyo; Ulayatilmiladiyyah, Nur; Trisnani, Syafinda Meisari; Octavia, Tania; Dewangga, Mahendra Wahyu (Bangladesh Journal of Medical Science, 2025)
Background Benefits of butterfly pea flowers have been widely studied and proven to be able to reduce total cholesterol levels in male Wistar white rats which had previously been made hypercholesterolemic. Aim Butterfly pea flowers contain active compounds in the form of flavonoids and anthocyanins, both of which act as antioxidants in reducing total cholesterol levels. This study aims to determine the effect of butterfly pea flower water extract on total cholesterol levels in male white Wistar rats induced by a high cholesterol diet. Methodology This research uses a posttest only control group design method. There were 3 groups divided randomly from 36 mice, namely the normal group (P0), the sick group (P1), the treatment group (P2). Group P0 was given standard feed and distilled water, group P1 was given a high cholesterol diet in the form of quail egg yolk, and group P2 was given a high cholesterol diet and given butterfly pea flower water extract at a dose of 600mg/kg BB. Rat blood samples were taken from the orbital sinus at the end of the study to measure total cholesterol levels using the CHODPAP method. Results: The mean total cholesterol levels for groups P0, P1, and P2 were 89.15 ± 2.44 mg/dL, 194.37 ± 3.64 mg/dL, and 108.86 ± 2.84 mg/dL, respectively. Data analysis used the One-Way Anova test followed by the Post Hoc LSD test. The results of the One-Way Anova test showed that there was a significant difference with a p value <0.05 (p=0.00). Post Hoc LSD test results showed significant differences between all groups with a p value <0.05 (p=0.00). Conclusion: The conclusion of this research is that butterfly pea flower extract has an effect on total cholesterol levels in male white Wistar rats fed a high cholesterol diet. BJMS, Vol. 24 No. 04 October’25 Page : 1114-1118